Utilization of Iron Scrap for Palm Oil Mill Effluent Treatment by Fenton and Foto-Fenton Processes - Diana Novita Sari; Dea Amelia; Muhammad David Ramadhon; Yuant Tiandho (JURNAL SAINS NATURAL, 2022)
The increase in the amount of palm oil production impacts increasing the total liquid waste from the processing of palm oil. Palm oil mill effluent (POME) has high chemical oxygen demand (COD) and biochemical oxygen demand (BOD) parameters that can cause environmental pollution. This study processed POME using the Fenton mechanism using reagents derived from scrap iron. The Fenton mechanism is one of the advanced oxidation process technology (AOPs) in wastewater treatment. To improve the performance of the Fenton mechanism, the researchers integrated it with UV-rays in the photo-Fenton mechanism scheme. Fenton and photo-Fenton processes effectively reduce the pH, BOD, and COD of POME. The COD removal efficiency was 99.91%, while the BOD removal efficiency was 99.93%. The more FeSO4 added to the wastewater, the more significant the reduction of BOD and COD in the Fenton and photo-Fenton processes. Also, photo-Fenton is more effective than the Fenton process to reduce BOD and COD in the POME.Keywords: POME; Fenton; Photo-Fenton; Scrap ironABSTRAKPemanfaatan Besi Bekas untuk Pengolahan Limbah Cair Industri Kelapa Sawit Melalui Proses Fenton dan Foto-FentonMeningkatnya jumlah produksi kelapa sawit, berdampak pada peningkatan total limbah cair dari hasil pengolahan kelapa sawit. Limbah cair industri kelapa sawit atau Palm Oil Mill Effluent (POME) memiliki nilai parameter chemical oxygen demand (COD) dan biochemical oxygen demand (BOD) yang tinggi sehingga dapat menyebabkan pencemaran lingkungan. Di dalam penelitian ini, dilakukan pengolahan POME menggunakan mekanisme Fenton menggunakan reagen yang berasal dari besi bekas. Mekanisme Fenton adalah salah satu pengembangan dari teknologi proses oksidasi maju (AOPs) dalam pengolahan air limbah.  Untuk meningkatkan performa dari mekanisme Fenton, peneliti mengintegrasikan system tersebut dengan sinar-UV dalam skema mekanisme foto-Fenton. Proses Fenton dan foto-Fenton sangat efektif dalam menurunkan pH, BOD dan COD dari POME. Efisiensi penyisihan COD mencapai 99,91%, sedangkan efisiensi penyisihan BOD mencapai 99,93%. Semakin banyak FeSO4 yang ditambahkan ke dalam air limbah maka semakin besar reduksi BOD dan COD dalam proses Fenton dan foto-Fenton. Selain itu, foto-Fenton lebih efektif dibandingkan dengan proses Fenton dalam mereduksi BOD dan COD dalam POMEKata kunci : POME; Fenton; foto-Fenton; besi bekas